Manajemen Pengembangan Karir Perawat Di RSUD Wonosari Gunungkidul Propinsi DIY - , WANDA ABRAR, Prof. dr. Adi Utarini, MSc, MPH, PhD ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Clinical nursing was less promoted area and received less guidance in the effort to achieve career development which was very useful to place nurses to certain position suitable to their specialities and to provide better chances. Goal: To explore hospital management policies and nursesâ understanding about professional career development of clinical nurses, and to identify career development pattern in Wonosari Hospital. Metode: This research was decriptive qualitative using purposive sampling in which indepth interview was conducted with hospital management and local government. It also involved Forum Group Discussion for a group of clinical nurses which was divided into 4 groups, and 1 interview group. Result and Discussion: The career structure of nurses in Wonosari Hospital still followed functional career structure of Civil Service, in which management did not have optimal role in guiding nursesâ career. There were many factors that influenced nurse career development such as career planning that most nurses in Wonosari Hospital did not understand. Hospital management also had mindset that physical career to improve revenues was more important the development of existing human resources. Lack of appreciation for nursesâ work performance led nurses to be less motivated to improve their career. Conclusion and Suggestion: The management career of Wonosari Hospital has not systematically developed and nursesâ career planning was still partially. Therefore, Wonosari Hospital management needs to create a systematic professional nursing career development together with Health Department, BKD, and PPNI of Gunungkidul regency.